1995
DOI: 10.1111/j.1399-3054.1995.tb05116.x
|View full text |Cite
|
Sign up to set email alerts
|

The timing of maize leaf senescence and characterisation of senescence‐related cDNAs

Abstract: The fiming of maize leaf senescence and characferisaiion oi setieseence-related cDNAs. -Physiol. Plant. 93: 67.V682.Leaf seneseenee was eharaeferised in fwo Zea mays lines, earlier senescence (ESl and later senescence (LSi. Loss of chlorophyll was delayed in LS compared with ES, but the decline in photosynthesis occurred simultanetiusly in fhe two lines. Western analysis defected transition points during senescence of both lines when major quantitative and qualitati\e changes oeeutTed in a number of leaf prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Life Sci. Differential screening of cDNAs from tomato [157], Arabidopsis [158], rape [159], strawberry [160], barley [161], maize [162] and Chlorella protothecoides (S. Hö rtensteiner, unpublished) have led to the isolation of a number of different senescence-related genes [8]. 56,1999 Review Article 341 also resemble senescence.…”
Section: Significance Of Chl Breakdownmentioning
confidence: 99%
“…Life Sci. Differential screening of cDNAs from tomato [157], Arabidopsis [158], rape [159], strawberry [160], barley [161], maize [162] and Chlorella protothecoides (S. Hö rtensteiner, unpublished) have led to the isolation of a number of different senescence-related genes [8]. 56,1999 Review Article 341 also resemble senescence.…”
Section: Significance Of Chl Breakdownmentioning
confidence: 99%
“…The loss in chlorophyll and decline in photosynthesis trigger leaf senescence (Smart 1994;Bleecker and Patterson 1997). Although leaf senescence is a degenerative process, it plays a vital role in nutrient recycling (Himelblau and Amasino 2001;Smart et al 1995). The released nutrients are transferred to actively growing young leaves and developing fruits and seeds (Gan 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Plants grown on nutrient solution containing low S and low N showed fewer deficiency symptoms than plants grown on solutions containing low S and high N; this effect of mineral N availability was largely explained by differences in growth rate (Blake-Kalff et al , 1998). In spite of these observations, in oilseed rape, there have been few published studies to determine if the S remobilization observed in response to sulphate deficiency (i) is related to the enhancement of leaf senescence processes as classically observed in the case of mineral N deficiency (Smart et al , 1995; Gombert et al , 2006; Lim et al , 2007) and (ii) differs as a function of mineral N availability.…”
Section: Introductionmentioning
confidence: 99%